Phenomenological Study of baryon-Resonance Production in Neutrino-Nucleon Scattering - Norman, Daniel A. (Tufts Archival Research Center, 2016)
Neutrino-nucleon interactions are a subject of great interest in modern physics. Baryon resonance reactions, characterized by the creation of a short-lived particle at the interaction vertex, represent a significant contribution to the total cross section of neutrino-nucleon scattering. The $Δ$(1232) particles, which decay into nucleons and pions, are known examples of resonance particles that carry baryon number =1. Bubble chamber experiments suggest there may be other baryon-resonance states with masses greater then that of the $Δ$ state. However, the presence of these higher mass resonance particles in neutrino-nucleon scattering is not established. The value of the axial vector mass of the resonance reaction is also not unknown. I reviewed several papers on $Δ$-resonance production phenomenology, and I used these papers to write a simulation of resonance production. In this Thesis I present the design of the simulation and results obtained with it. Experimental research groups use GENIE, a Monte Carlo program, to generate neutrino-nucleon interaction events. By comparing the results of my simulation to GENIE predictions, I obtain evidence for the existence of higher-mass baryon resonance states. I also present new constraints on the value of the axial vector mass for baryon-resonance reactions within the context of contemporary resonance production phenomenology.